2021
DOI: 10.1002/ece3.7133
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and evolution of chloroplast tRNAs in Adoxaceae

Abstract: Chloroplasts are semiautonomous organelles found in photosynthetic plants. The major functions of chloroplasts include photosynthesis and carbon fixation, which are mainly regulated by its circular genomes. In the highly conserved chloroplast genome, the chloroplast transfer RNA genes (cp tRNA) play important roles in protein translation within chloroplasts. However, the evolution of cp tRNAs remains unclear. Thus, in the present study, we investigated the evolutionary characteristics of chloroplast tRNAs in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…The molecular markers such as highly divergent regions and repeat sequences derived from the entire plastome sequence hold promise for use in species delimitation and population genetics [ 29 31 ]. Moreover, the comparison of complete plastome sequences further provides the opportunity to explore sequence variation and molecular evolutionary patterns associated with gene loss, rearrangements, duplication, and transfer events [ 32 34 ]. Until now, plastomes have only been used for comparative analyses of single species of Fagopyrum or a few species of the genus [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular markers such as highly divergent regions and repeat sequences derived from the entire plastome sequence hold promise for use in species delimitation and population genetics [ 29 31 ]. Moreover, the comparison of complete plastome sequences further provides the opportunity to explore sequence variation and molecular evolutionary patterns associated with gene loss, rearrangements, duplication, and transfer events [ 32 34 ]. Until now, plastomes have only been used for comparative analyses of single species of Fagopyrum or a few species of the genus [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that the introns in chloroplast tRNA Val of Gossypium populifolium and Zea mays aggregated to the same branch (Figure 3), suggesting that the introns of corn and cotton have a close phylogenetic relationship. Additionally, chloroplast tRNAs with introns were grouped with cyanobacteria, providing supportive evidence for a common cyanobacterial lineage source of cp tRNAs [58].…”
Section: Discussionmentioning
confidence: 75%
“…tRNA Leu and tRNA Ser were observed to have 80 nt or more. These two tRNA isotypes were also found to harbor more than 83 nt in Adoxaceae plants, which shows that the gene sequences of tRNA Ser and tRNA Leu are longer than other tRNAs [58]. In addition, some tRNA isoacceptors were not observed in the cp genome of Gossypium, which was similar to that of the species in Gramineae [28].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The molecular markers such as highly divergent regions and repeat sequences derived from the entire plastome sequence hold promise for use in species delimitation and population genetics [29][30][31]. Moreover, the comparison of complete plastome sequences further provides the opportunity to explore sequence variation and molecular evolutionary patterns associated with gene loss, rearrangements, duplication, and transfer events [32][33][34]. Until now, plastomes have only been used for comparative analyses of single species of Fagopyrum or a few species of the genus.…”
Section: Introductionmentioning
confidence: 99%